Effects of Firm Size and Capital Structure on Firm Value (Empirical Study of Telecommunication Companies Listed on the Indonesia Stock Exchange for 2018-2021) - Mahirah, Annisaa; Uzliawati, Lia; Soleha, Nurhayati (Review of Accounting and Taxation, 2023)
Purpose - The purpose of this study is to determine the effect of firm size and capital structure on firm value using data from telecommunication companies listed on the Indonesia Stock Exchange in 2018-2021. Design/methodology/approach - The method used is quantitative research with secondary data from 16 companies. The sample was taken using the purposive sampling method. This study used a multiple linear regression. Finding - According to the research findings, (1) firm size has a significant positive impact and (2) capital structure does not. In this research model, the value of determination (R squared) is 0.110 or 11%. The calculated F value is 3.202 > 3.175 and the sig F value is 0.049 < 0.05. Originality -